The Use of Flashcards in Improving Vocabulary Mastery of Students with Disability - Habibi, Nugroho (INKLUSI, 2017)
This research comes from the weakness of vocabulary mastery of students with disability. This researcher used Classroom Action Research (CAR) in integrated classroom to improve vocabulary of the students with disability at the second grade of SMP Diponegoro, Junrejo, Batu in the academic year 2017/2018 by using flashcards. In this research, the researcher becomes a teacher while the English teacher becomes a volunteer or therapist to help, control and manage the class. The result of the study showed that before the implementation of flashcards, all students with disability’ score were under 75, with the lowest score was 50 and the highest score was 70. From six students with disability, no one passed Standard Minimum Criteria (KKM). Therefore, in the cycle 1, all students with disability passed Standard Minimum Criteria (KKM). The lowest score was 80 and the highest score was 100.[Penelitian ini berasal dari kelemahan kosakata siswa berkebutuhan khusus. Peneliti ini menggunakan Penelitian Tindakan Kelas (PTK) dikelas integrasi untuk meningkatkan kosakata siswa berkebutuhan khusus dikelas dua SMP Diponegoro, Junrejo, Batu tahun ajaran 2017/2018 dengan  menggunanakan flashcards. Dalam penelitian ini, peneliti berperan menjadi guru sementara itu guru bahasa Inggris menjadi relawan atau terapi untuk membantu, mengontrol dan mengatur kelas. Hasil dari penelitian ini menunjukkan bahwa sebelum implementasi flashcrads, nilai seluruh siswa berkebutuhan kusus dibawah 75, dengan nilai terrendah adalah 50 dan nilai tertinggi adalah 70. Dari enam siswa berkebutuhan khussu, tidak siswa ada yang melewati Kriteria ketuntatas minimal (KKM). Oleh karena itu, pada siklus 1, semua siswa berkebutuhan khusus melewati kriteria ketuntasan minimal (KKM). Dengan nilai terrendah 80 dan nilai tertinggi adalah 100.]